Reconstruction of the human nipple–areolar complex: a tissue engineering approach - Maistriaux, Louis; Foulon, Vincent; Fievé, Lies; Xhema, Daela; Evrard, Robin; Manon, Julie; Coyette, Maude; Bouzin, Caroline; Poumay, Yves; Gianello, Pierre; Behets, Catherine; Lengelé, Benoît (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Nipple–areolar complex (NAC) reconstruction after breast cancer surgery is challenging and does not always provide optimal long-term esthetic results. Therefore, generating a NAC using tissue engineering techniques, such as a decellularization–recellularization process, is an alternative option to recreate a specific 3D NAC morphological unit, which is then covered with an in vitro regenerated epidermis and, thereafter, skin-grafted on the reconstructed breast. Materials and methods: Human NACs were harvested from cadaveric donors and decellularized using sequential detergent baths. Cellular clearance and extracellular matrix (ECM) preservation were analyzed by histology, as well as by DNA, ECM proteins, growth factors, and residual sodium dodecyl sulfate (SDS) quantification. In vivo biocompatibility was evaluated 30 days after the subcutaneous implantation of native and decellularized human NACs in rats. In vitro scaffold cytocompatibility was assessed by static seeding of human fibroblasts on their hypodermal side for 7 days, while human keratinocytes were seeded on the scaffold epidermal side for 10 days by using the reconstructed human epidermis (RHE) technique to investigate the regeneration of a new epidermis. Results: The decellularized NAC showed a preserved 3D morphology and appeared white. After decellularization, a DNA reduction of 98.3% and the absence of nuclear and HLA staining in histological sections confirmed complete cellular clearance. The ECM architecture and main ECM proteins were preserved, associated with the detection and decrease in growth factors, while a very low amount of residual SDS was detected after decellularization. The decellularized scaffolds were in vivo biocompatible, fully revascularized, and did not induce the production of rat anti-human antibodies after 30 days of subcutaneous implantation. Scaffold in vitro cytocompatibility was confirmed by the increasing proliferation of seeded human fibroblasts during 7 days of culture, associated with a high number of living cells and a similar viability compared to the control cells after 7 days of static culture. Moreover, the RHE technique allowed us to recreate a keratinized pluristratified epithelium after 10 days of culture. Conclusion: Tissue engineering allowed us to create an acellular and biocompatible NAC with a preserved morphology, microarchitecture, and matrix proteins while maintaining their cell growth potential and ability to regenerate the skin epidermis. Thus, tissue engineering could provide a novel alternative to personalized and natural NAC reconstruction.